The Impact Of Knowledge Management On Developing Administrative Creativity Among Civil Sectors In North Al Batinah In The Sultanate Of Oman: Transformationa Leadership As A Mediating Variable - Khalid Mohammed Ahmed Al Sadi; Mohammad Nashief s. Disomimba; Kalsom Ali (OCERINT International Organization Center of Academic Research, 2024)
Volume 8, Issue 24 (page: 699 - 721)